Effects of Exchange Rate and World Prices on Export Price of Vietnamese Coffee - Hong, To Thi Kim (International Journal of Economics and Financial Issues, 2016)
Identifying factors of export price fluctuation in agricultural products is necessary to equip decision makers and producers with bases and tools in forecasting price fluctuation and then suggesting solutions for risk mitigation. This research integrated quantitative and qualitative methods to analyze and measure effects of some major factors on export price of Vietnamese coffee. The data of 34 years from 1981-2014 shows that coffee price have fluctuated with a cycle of 5-year increase and 7-year decrease. The study found major factors of the price fluctuation are exchange rate and export prices of other exporting countries like Brazil and Colombia. Export price of Brazilian coffee made a positive effect on the price of Vietnamese suggesting a competition between two countries in the world coffee market while Colombian coffee occupied its own market share. To promote sustainable growth in exports, Vietnamese coffee needs to maintain stable markets and invest more on branding and product quality to improve its competition capacity. Keywords: price, coffee, export, Vietnam, fluctuation JEL Classifications: F140, L110, M210